2015
DOI: 10.1186/s12885-015-1558-5
|View full text |Cite
|
Sign up to set email alerts
|

The burden of cervical pre-cancer and cancer in HIV positive women in Zambia: a modeling study

Abstract: BackgroundHIV infection is associated with a higher incidence of precancerous cervical lesions and their progression to invasive cervical cancer (ICC). Zambia is a global epicenter of HIV and ICC, yet the overall burden of cervical pre-cancer [cervical intraepithelial neoplasia 3 (CIN3)] and ICC among its HIV positive adult female population is unknown. The objective of this study was to determine the burden of cervical disease among HIV positive women in Zambia by estimating the number with CIN3 and ICC.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
0
29
4
Order By: Relevance
“…Specifically, 3% of women were diagnosed with ICC and 13% with high-grade CIN. It should be noted that the burden of cervical disease in our study was somewhat lower than in previously published Zambian studies, which have reported that ∼30-50% of HIV-infected women are VIA/DC positive, 18,19 20% have CIN2+, 19 and 53% are hrHPV positive. 20 These studies were conducted before cART was widely available in Zambia and before the introduction of the so-called Option B+ strategy (through which the overwhelming majority of HIV-infected women of reproductive age have obtained access to cART regardless of their CD4+ cell count), possibly accounting for the observed differences.…”
Section: Discussioncontrasting
confidence: 78%
“…Specifically, 3% of women were diagnosed with ICC and 13% with high-grade CIN. It should be noted that the burden of cervical disease in our study was somewhat lower than in previously published Zambian studies, which have reported that ∼30-50% of HIV-infected women are VIA/DC positive, 18,19 20% have CIN2+, 19 and 53% are hrHPV positive. 20 These studies were conducted before cART was widely available in Zambia and before the introduction of the so-called Option B+ strategy (through which the overwhelming majority of HIV-infected women of reproductive age have obtained access to cART regardless of their CD4+ cell count), possibly accounting for the observed differences.…”
Section: Discussioncontrasting
confidence: 78%
“…Although WHO 2013 guidance does not include thermo‐coagulation as a treatment modality, there is growing use of and support for thermo‐coagluation in a number of LMIC settings . As evidence accumulates for non‐inferior outcomes for thermo‐coagluation pre‐cancers compared to other treatment modalities, guidance should be reviewed and updated.…”
Section: Discussionmentioning
confidence: 99%
“…Although WHO 2013 guidance does not include thermo-coagulation as a treatment modality, there is growing use of and support for thermo-coagluation in a number of LMIC settings. 12,13,[31][32][33] As evidence accumulates for noninferior outcomes for thermo-coagluation pre-cancers compared to other treatment modalities, 12,24,34 guidance should be reviewed and updated. Similarly, health care planners in LMICs should consider inclusion of thermo-coagulation in strategic planning for long-term cost-effectiveness and sustainable delivery of screening programmes.…”
Section: Implications For Practice Policy and Researchmentioning
confidence: 99%
“…Compared to cobas in the entire population, OncoE6 was less sensitive but more specific. The high specificity makes it possible to be applied to screening high HPV‐prevalence, high‐risk populations, such as cervical cancer screening in HIV‐infected women . Moreover, OncoE6 might be used for primary screening in LMICs in place of VIA, which is already being widely used, to achieve a similar or superior sensitivity but higher specificity to reduce colposcopy referral numbers and avoiding overtreatment under an already over burdened health‐care system in LMICs.…”
Section: Discussionmentioning
confidence: 99%